2007
DOI: 10.1002/adfm.200600497
|View full text |Cite
|
Sign up to set email alerts
|

Selective Immobilization of Nanoparticles on Surfaces by Molecular Recognition using Simple Multiple H‐bonding Functionalities

Abstract: Using a complementary pair of simple alkylthiolates with hydrogen‐bonding moieties, functionalized Au55 clusters could be selectively deposited onto self‐assembled monolayers on gold that carry the opposite functionality. The deposition can be readily controlled by the medium in which the clusters are dissolved and by the density of the functionalities in the self‐assembled monolayers, and yields single clusters as well as two‐dimensional cluster assemblies on the surface. The clusters are sufficiently strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 54 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…[24b,c,33] Noble metal nanoparticles, especially in the size range <10 nm, have unique optical, magnetic, catalytic, as well as potential biological applications . Various approaches have been demonstrated to achieve self‐assembled thin films of nanoparticles on substrates using partial ligand exchange, layer‐by‐layer exchange, electrostatic stabilization, DNA base pairing, or complementary hydrogen bonding . Similarly, electrostatic assembly of equally sized gold and silver nanoparticles, binary nanoparticle superlattices, and virus‐nanoparticle hybrid crystals have shown to self‐assemble into unprecedented crystal morphologies .…”
Section: Monolayer Protected Metal Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…[24b,c,33] Noble metal nanoparticles, especially in the size range <10 nm, have unique optical, magnetic, catalytic, as well as potential biological applications . Various approaches have been demonstrated to achieve self‐assembled thin films of nanoparticles on substrates using partial ligand exchange, layer‐by‐layer exchange, electrostatic stabilization, DNA base pairing, or complementary hydrogen bonding . Similarly, electrostatic assembly of equally sized gold and silver nanoparticles, binary nanoparticle superlattices, and virus‐nanoparticle hybrid crystals have shown to self‐assemble into unprecedented crystal morphologies .…”
Section: Monolayer Protected Metal Nanoparticlesmentioning
confidence: 99%
“…However, when the two particles are closer than a few nanometers (i.e., involving non‐DLVO forces such as hydration, hydrophobic, and solvation forces), the classical DLVO theory is not applicable . Despite these challenges, considerable progress has been made using surface‐functionalized colloidal particles, using restricted volume, depleted forces, electrostatic interactions, DNA hybridization, hydrogen bonding (H‐bonding), and even the designer inorganic or polymeric patchy particles to control interactions and to achieve higher order assemblies . The self‐assembly of microparticles using DNA hybridization approach suggested that by tuning the strength of H‐bonding (e.g., tuning the DNA melting temperature), it is possible to obtain either random aggregates due to irreversible snapping (i.e., strong H‐bonding) or well‐ordered macroscopic crystals by H‐bonding rearrangement (i.e., weak H‐bonding) from micrometer sized spherical particles …”
Section: Introductionmentioning
confidence: 99%
“…The same strategy has been used for the fabrication of layers of self-assembled semiconductor nanocrystals on appropriate electrodes 227 or for selective immobilization of metal nanocrystals on functionalized surfaces. 228 Later, the molecular recognition concept was extended to the design and preparation of conjugated polymers/ semiconductor nanocrystals hybrids. De Girolamo et al prepared a solution processable regioregular poly (alkylthiophene) derivative containing diaminopyrimidine side groups, namely poly(3-hexylthiophene-co-3-(6-oxy-2,4-diaminopyrimidine)hexylthiophene) (P3HT-co-P3(ODAP)HT).…”
Section: Hybrid Materials From Semiconductor Nanocrystals and Conjuga...mentioning
confidence: 99%
“…Among the various approaches for biorecognition, the principle of using hydrogen bonds to confer binding strength and selectivity is of particular interest [92][93][94][95][96], mainly owing to their relative flexibility in geometry compared with rigid covalent bonds [97,98]. Because guest molecules of biological interest may possess various numbers of proton-donating and/or proton-accepting groups, the design and syntheses of host receptors providing multiple hydrogen-bonding sites are necessary to maximize the recognition capacity.…”
Section: Multiple Hydrogen Bonds Tuning the Guest/host Excited-state mentioning
confidence: 99%